Approximate Riemann Solver for the Electronic M1 Model Without Electric Field in the Diffusive Limit. Issue 6 (18th September 2016) - Guisset, S.; Brull, S.; Dubroca, B.
ABSTRACT: This work is devoted to the derivation of an approximate Riemannsolver for the electronic M 1 model without electric field in the diffusive regime. The derivation of the scheme is based on an approximate Riemann solver, where the intermediate states are chosen consistent with the integral form of the approximate Riemann solver. This choice can be modified to enable the derivation of a numerical scheme which satisfies the admissible conditions and enjoys asymptotic-preserving properties recovering the correct diffusion equation. Numerical tests cases are presented and the asymptotic-preserving scheme is compared to the classical HLL (Harten et al., 1983 ) scheme usually used for the electronic M 1 model.